Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/jcm11185333
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic Variability in Subjects with Diabetes and Hypogonadism during Testosterone Replacement Treatment: A Pilot Study

Abstract: Background: This is a proof of concept, as a pilot study, with the aim to evaluate continuous glucose monitoring metrics (CGM) in subjects with type 2 diabetes (T2DM), treated with nutritional therapy and metformin, before and after testosterone replacement therapy (TRT). Methods: In this longitudinal observational study, subjects affected by T2DM and starting TRT for documented ED and hypogonadism were enrolled. All subjects mounted a CGM system during the v0 visit, one week before the beginning of the TRT (w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Considering male hypogonadism, several cross‐sectional studies reported up to 40% of men with T2DM exhibit low testosterone levels [ 2 ]. A recent study conducted by Defeudis et al [ 26 ], evaluated the effect of testosterone replacement therapy (TRT) on glycemic control and variability measured with aCGM, in people with T2DM and ED. The authors found no significant differences in TIR, time above range (TAR, > 140 mg/dL), time below range (TBR, < 70 mg/dL), estimated HbA1c, area under the curve (AUC) for blood glucose values above and below the target during the intervention period.…”
Section: Methodsmentioning
confidence: 99%
“…Considering male hypogonadism, several cross‐sectional studies reported up to 40% of men with T2DM exhibit low testosterone levels [ 2 ]. A recent study conducted by Defeudis et al [ 26 ], evaluated the effect of testosterone replacement therapy (TRT) on glycemic control and variability measured with aCGM, in people with T2DM and ED. The authors found no significant differences in TIR, time above range (TAR, > 140 mg/dL), time below range (TBR, < 70 mg/dL), estimated HbA1c, area under the curve (AUC) for blood glucose values above and below the target during the intervention period.…”
Section: Methodsmentioning
confidence: 99%